Reducción de costos de carguío, mediante la implementación de un sistema de gestión de gets, en Andes Peru Gold - Huamachuco - Narciso Nontol, Blanca Antonella (2019)
Mineral exploitation processes require heavy machinery for loading, including excavators and front loaders. Being the 450 Volvo excavator and the L150H Volvo front loader. With this equipment, material loading, truck transportation, removal of top soil among other activities are carried out. Both the excavator and the loader attack the ground with the bucket and metal teeth or nails (GETS) are needed to facilitate the process of separating or breaking the material to achieve loading. The teeth are consumables that wear out until they are broken by constant use. For the present study, an analysis of 25,000 hours of operation of the equipment was analyzed, from which it was concluded that the consumption of Gets can be approximately 50% of the value of the equipment. This work proposes to develop and implement a management system that allows to reduce the cost of using the GETS of excavators and front loaders based on the efficiency and effectiveness of the use of material, economic, human and time resources oriented to mining. Through the GETS wear monitoring process, the company will be able to have objective information on wear and will be able to manage the duration and timely change of the consumables, seeking to extend their useful life and reduce maintenance costs. Chapter 1 presents introductory aspects of the project, the theoretical framework. A description of the equipment used, materials and methods is made in Chapter 2. The results and discussions in chapter 3 and finally in chapter 4 the conclusions and recommendations are presented.